XVIII World Congress of Sociology, Yokohama, Japan, 13-19 July 2014 - (ISA), International Sociological Association (Journal of Sociocybernetics, 2014)
XVIII World Congress of Sociology : “Facing an unequal world: Challenges for Global Sociology”, Yokohama, Japan, 13-19 July 2014The Program of the World-Congress is now avialable on the official ISA-Website: the official ISA-Website For more details regarding the sessions organised by RC51 please have a look on the RC51-Website